Consumer Behavior in the Era of TikTok Shop and Instagram Commerce: A Meta-Review of Determinants of Impulse Buying - Suci Nofita Sari; Febrina Anandari; Zefriyenni, Zefriyenni (Sean Institute, 2025)
This study examines the phenomenon of Impulsive Buying on the TikTok Shop platform, one of the booming e-commerce platforms in Indonesia. The research adopts a qualitative approach with secondary data from sources such as literature, surveys, and relevant publications. The findings reveal that the phenomenon of Impulsive Buying is significant on TikTok Shop, influenced by factors such as consumer characteristics and lifestyle, price perception, motivation, promotions, discounts, and positive emotions that drive spontaneous purchases. While several previous studies attempted to explore the influence of religiosity on impulsive buying behavior, the results have been inconsistent. Thus, this research offers new insights into consumer behavior within the scope of e-commerce in the era of Industry 4.0, particularly in the context of the TikTok Shop platform.